Host-specific microbiomes of blow flies: ecological drivers and implications for pathogen carriage - Mikaelyan, Aram; Receveur, Joseph; Bernstein, Kadie; Babcock, Nicholas J.; Pechal, Jennifer L.; Welsh, Michael V.; Waters, Kelly A.; Yoskowitz, Katherine H.; Benbow, M. Eric (Frontiers in Immunology, 2025)
Blow flies (Lucilia sericata and Phormia regina) are necrophagous insects that interact with dense microbial reservoirs and are opportunistic vectors of human and animal pathogens. Despite constant exposure to diverse environmental microbes, it is unclear whether their bacterial communities are primarily acquired stochastically or shaped by host factors that could influence pathogen carriage. We conducted a systematic comparison of wild L. sericata and P. regina collected from seven cities across an urban-rural gradient to determine whether microbiome composition is structured by host species identity or environmental variables. Using 16S rRNA gene sequencing of individual flies, we profiled bacterial communities and applied alpha- and beta-diversity analyses, PERMANOVA, and Random Forest classification to quantify species-level microbiome differentiation. Species identity was the strongest predictor of microbiome composition (PERMANOVA, p = 0.001), while location, land cover type, sampling month, and sex had no significant effects. Random Forest modeling identified multiple bacterial taxa that consistently distinguished the two species, including Ignatzschineria and Dysgonomonas, which were enriched in P. regina, and Vagococcus and Escherichia-Shigella, which were enriched in L. sericata. These taxa are of clinical relevance, with Ignatzschineria in particular increasingly reported from human myiasis and soft-tissue infections, sometimes exhibiting antimicrobial resistance. Our findings demonstrate that wild blow flies maintain species-specific microbiomes despite shared environments, suggesting that host identity strongly filters microbial communities. The presence of opportunistic pathogens within these structured microbiomes underscores the need to understand how blow fly–microbe associations contribute to pathogen persistence and dissemination. By revealing predictable, species-dependent microbiome patterns, this study highlights potential targets for microbiome-based strategies aimed at mitigating blow fly–associated disease risks.